A self-templating method for metal–organic frameworks to construct multi-shelled bimetallic phosphide hollow microspheres as highly efficient electrocatalysts for hydrogen evolution reaction. Issue 14 (21st March 2019) - Du, Yunmei; Zhang, Mingjuan; Wang, Zuochao; Liu, Yanru; Liu, Yongjun; Geng, Yanling; Wang, Lei
Abstract : Hydrogen evolution reaction (HER) via electrocatalysis using cost-efficient bimetallic phosphide as electrocatalyst holds a great promise for environmentally friendly energy technologies. Abstract : Hydrogen evolution reaction (HER) via electrocatalysis using cost-efficient bimetallic phosphide as electrocatalyst holds a great promise for environmentally friendly energy technologies. Here we report a novel strategy to synthesize a series of CoNiP multi-shelled hollow microspheres with different ratios of Co to Ni using metal–organic framework as both the precursor and the template, and the as-obtained CoNiP-0.25 presents a pre-eminent electrocatalytic activity for the hydrogen evolution reaction (HER) in 1.0 M KOH. The CoNiP-0.25 microspheres are found to drive 20 mA cm −2 at a potential of 170 mV vs. RHE, which is 120 mV and 59 mV smaller than that of pure NiP and CoP, respectively. The outstanding HER activity of the CoNiP-0.25 microspheres can be attributed to the optimization of their electronic structure, the typical multi-shelled hollow structure and the massive exposure of the active phase bimetallic phosphide CoNiP. Moreover, the enhanced electrochemical stability of CoNiP electrocatalyst might also stem from its special structure of multi-shelled hollow microsphere, which inhibits its superficial oxidation during the catalytic process.